A method for lithium metal negative electrode strip cutting based on low-temperature micro-embossing and edge in-situ passivation and lithium metal negative electrode sheet
Patent Information
- Application Number
- CN202611309605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-13
AI Technical Summary
[0009]本申请的目的在于提供一种基于低温微压印与边缘原位钝化的锂金属负极带材裁切的方法和锂金属负极片,以解决解决锂金属裁切易产生毛刺、碎屑、塑性变形及边缘界面不稳定等难题
本申请提供了一种基于低温微压印与边缘原位钝化协同的锂金属负极带材裁切方法,通过低温脆化、纳米级刃口微压印裁切以及刃口可消耗/可转移保护薄膜三者协同作用,实现低损伤、无热影响、边缘平整的锂金属负极带材裁切。低温环境使锂金属由塑性转变为脆性,结合纳米级刃口的微压印裁切,可有效抑制塑性变形,避免卷边、毛刺及整体变形;同时该过程为纯物理过程,无需化学试剂,且无高能量输入,彻底消除了热影响区。此外,裁切瞬间即可对新暴露的锂边缘进行原位钝化保护,避免了后续单独处理的复杂工序,解决了现有裁切技术无法在裁切同时主动保护新鲜边缘的关键缺陷,有效提升了裁切后锂负极的循环寿命;刃口所携带的可消耗/可转移保护薄膜可避免硬接触损伤,并在后续化成阶段参与构筑稳定SEI膜。该方法克服了传统裁切工艺损伤大、界面差、易污染等问题,适用于高安全、长循环锂金属电池的工业化生产。
Smart Images

Figure CN122895811A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, and in particular to a method for cutting lithium metal anode strips and lithium metal anode sheets based on low-temperature microimprinting and in-situ edge passivation. Background Technology
[0002] Lithium metal anodes, with their theoretical specific capacity of up to 3860 mAh / g, are considered key anode materials for achieving high-energy-density battery systems. All-solid-state batteries, assembled from high-nickel, high-voltage cathodes, lithium metal anodes, and solid-state electrolytes, not only have significantly higher energy densities than traditional liquid lithium-ion batteries but also offer greatly improved safety, thus being widely recognized as one of the mainstream technologies for next-generation high-energy-density power batteries.
[0003] However, the large-scale application of lithium metal anodes is still limited by several engineering challenges, with the cutting and processing technology being one of the major bottlenecks. Due to the soft texture and extremely high chemical reactivity of lithium metal, its cutting process is highly sensitive to processing conditions, and existing cutting methods generally have insurmountable technical defects.
[0004] Under mechanical stamping / cutting, the edges of lithium strips are prone to severe plastic deformation, curling and burrs, which increases the actual surface area of lithium and induces dendrite growth and interface side reactions. At the same time, improper stamping pressure control can easily lead to uneven thickness or even fracture, and the die wear rate is fast, which seriously affects the consistency and economy of processing.
[0005] While laser cutting can achieve non-contact processing, the high-energy laser beam will generate a significant heat-affected zone in the cutting area, causing lithium metal to melt, oxidize, and even generate byproducts such as Li2O and Li3N, which seriously impairs electrochemical activity. In addition, cutting spatter may pollute the surrounding area, and the equipment cost is high, which is not conducive to large-scale application.
[0006] Chemical etching relies on corrosive chemicals such as acids or organic solvents, which leads to difficulties in wastewater treatment and environmental pollution risks. At the same time, the etching process is complex and difficult to control precisely, which can easily introduce impurities or change the chemical state of the lithium surface, affecting subsequent electrochemical performance.
[0007] The above-mentioned cutting methods also face a common problem: the fresh lithium edges exposed after cutting have extremely high chemical activity, and are prone to side reactions with air, moisture or electrolyte during storage or battery assembly, forming an unstable solid electrolyte interface film, which further degrades battery performance.
[0008] Therefore, there is an urgent need to provide a method for cutting lithium metal anode strips to solve the above problems. Summary of the Invention
[0009] The purpose of this application is to provide a method for cutting lithium metal anode strips and lithium metal anode sheets based on low-temperature micro-imprinting and in-situ edge passivation, so as to solve the problems of burrs, chips, plastic deformation and unstable edge interfaces that are easy to generate during lithium metal cutting.
[0010] To achieve the above objectives, the first aspect of this application provides a method for cutting lithium metal anode strips based on low-temperature microimprinting and in-situ edge passivation, comprising: The lithium metal anode strip was subjected to low-temperature treatment to obtain a brittle lithium metal strip. Using a cutting die with nanoscale cutting edge, the brittle lithium metal strip is cut at a low temperature, low oxygen and low humidity protective atmosphere along a direction at an angle to the vertical to obtain the cut lithium metal anode strip. The cutting die with nanoscale cutting edge includes a cutting edge substrate and a functional protective film disposed on the surface of the cutting edge substrate. The functional protective film is in direct contact with the brittle lithium metal strip during the low-temperature micro-imprint cutting. The functional protective film includes at least one of polymer flexible film, low melting point alloy film, and fluorine-containing silicon organic-inorganic composite film.
[0011] Optionally, the low-temperature treatment is performed at a temperature of -20°C to -35°C for 5-6 minutes.
[0012] Optionally, the radius of the nanoscale cutting edge is <1 μm.
[0013] Optionally, the included angle of inclination is 30-70°.
[0014] Optionally, the temperature of the low-temperature micro-imprint cutting is -25℃ to -35℃, and the pressure is 0.995-0.105MPa.
[0015] Optionally, during the low-temperature micro-imprint cutting, the downward speed of the cutting die with nanoscale cutting edge is 0.01-0.02 mm / s.
[0016] Optionally, the temperature in the low-temperature, low-oxygen, and low-humidity protective atmosphere is -25°C to -35°C, with an oxygen content ≤10ppm and a moisture content ≤5ppm.
[0017] Optionally, the raw materials for the polymer flexible film include polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyoxyethylene copolymer, acrylonitrile copolymer, and acrylate polymer.
[0018] Optionally, the raw materials for the low-melting-point alloy film include bismuth-indium alloy, tin-bismuth-indium ternary alloy, and alkali metal alloy; In the bismuth-indium alloy, the mass ratio of bismuth to indium is 30-40:60-70; In the tin-bismuth-indium ternary alloy, the mass fractions of tin, bismuth, and indium are 12%-20%, 30%-35%, and 48%-55%, respectively. The alkali metal alloy includes at least one of lithium-sodium binary alloy, lithium-potassium binary alloy, and lithium-sodium-potassium ternary eutectic alloy.
[0019] Optionally, the raw materials for the fluorinated silicon organic-inorganic composite film include fluorinated silane modified SiO2, TiO2-doped polyvinylidene fluoride, and perfluoropolymer-silicate; The mass ratio of fluorinated silane to nano-SiO2 in the fluorinated silane-modified SiO2 is 1:5-15. The mass ratio of nano-TiO2 to PVDF in the TiO2-doped polyvinylidene fluoride is 1:8-20. The mass ratio of perfluoropolymer to silicate matrix in the perfluoropolymer-silicate is 3-7:3-7.
[0020] The second aspect of this application provides a lithium metal anode sheet, which is cut by the method for cutting lithium metal anode strips based on low-temperature microimprinting and in-situ edge passivation.
[0021] Compared with the prior art, the beneficial effects of this application include: This application provides a lithium metal anode strip cutting method based on the synergy of low-temperature microimprinting and in-situ edge passivation. Through the synergistic effect of low-temperature embrittlement, nanoscale edge microimprinting cutting, and a consuming / transferable protective film on the edge, low-damage, heat-affected zone (HAZ) lithium metal anode strip cutting is achieved, resulting in smooth edges. The low-temperature environment transforms lithium metal from plastic to brittle. Combined with nanoscale edge microimprinting cutting, plastic deformation is effectively suppressed, avoiding edge curling, burrs, and overall deformation. Simultaneously, this process is purely physical, requiring no chemical reagents and no high-energy input, completely eliminating the HAZ. Furthermore, in-situ passivation protection of the newly exposed lithium edges is applied instantly during cutting, avoiding complex subsequent processing steps. This solves the key defect of existing cutting technologies that cannot actively protect fresh edges during cutting, effectively improving the cycle life of the cut lithium anode. The consuming / transferable protective film carried by the edge prevents hard contact damage and participates in the construction of a stable SEI film during subsequent formation stages. This method overcomes the problems of large damage, poor interface, and easy contamination in traditional cutting processes, and is suitable for the industrial production of high-safety, long-cycle lithium metal batteries.
[0022] The lithium metal anode sheet provided in this application has a protective layer formed in situ at its edge, the edge plastic deformation is less than 5 μm, and there are no visible burrs or curled edges. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0024] Figure 1 A schematic diagram of the nanoscale cutting edge provided in this application; Figure 2 This is a schematic diagram of a traditional vertical shear blade. Detailed Implementation
[0025] First, the solution provided in this application will be explained in more detail as follows: The first aspect of this application provides a method for cutting lithium metal anode strips based on low-temperature microimprinting and in-situ edge passivation, including: The lithium metal anode strip was subjected to low-temperature treatment to obtain a brittle lithium metal strip. Using a cutting die with nanoscale cutting edge, the brittle lithium metal strip is cut at a low temperature, low oxygen and low humidity protective atmosphere along a direction at an angle to the vertical to obtain the cut lithium metal anode strip. The cutting die with nanoscale cutting edge includes a cutting edge substrate and a functional protective film disposed on the surface of the cutting edge substrate. The functional protective film is in direct contact with the brittle lithium metal strip during the low-temperature micro-imprint cutting. The functional protective film includes at least one of polymer flexible film, low melting point alloy film, and fluorine-containing silicon organic-inorganic composite film.
[0026] It is important to note that the functional protective film must meet multiple constraints: In terms of interface compatibility, the film must form a strong bond with the die edge while exhibiting weak affinity / weak reactivity with lithium metal, avoiding lithium adhesion, corrosion, and damage to the intrinsic structure of lithium; in terms of mechanical compatibility, it must maintain sufficient flexibility and toughness at low temperatures to buffer hard contact with the die edge without affecting the cutting effect due to stress concentration at the nano-die edge; in terms of functional synergy, it must provide anti-scratch, anti-burr, and anti-chip functions during the cutting process, and be wetted, swollen, and transformed by the electrolyte during battery formation, ultimately participating in the construction of a stable SEI film without residue; in terms of film formation and loading, a uniform, ultra-thin, and defect-free layer must be formed on the side of the wedge-shaped micro-die edge, with controllable thickness and without altering the die edge geometry; in terms of system compatibility, it must be highly compatible with lithium metal, electrolyte, low-temperature processes, and high-voltage / long-cycle battery systems, without introducing side reactions or foreign matter.
[0027] It should also be noted that the functional protective film also has the following functions: (1) During the imprinting of lithium metal electrode sheets, the direct hard contact between the die edge and lithium metal can be isolated, avoiding the cutting edge from scratching the lithium foil and preventing the generation of burrs or debris. (2) The material has a weak affinity or a controllable weak reaction with lithium metal, which neither destroys the intrinsic structure of lithium nor does it adhere to the lithium surface. (3) During the battery assembly and formation stage, it can be wetted, swollen, partially dissolved or transformed in situ by the electrolyte, and finally participate in the construction of a highly stable and flexible SEI film. At the same time, it is consumed or transferred layer by layer without any residual foreign matter.
[0028] In addition, the impact of low-temperature environment on the performance of functional protective film has been addressed through targeted design: polymer flexible film, low-melting-point alloy film, and fluorine-silicon organic-inorganic composite film are selected to ensure good flexibility and adhesion at -30℃, in order to cope with the increase in modulus and decrease in flexibility caused by low temperature; low temperature reduces the reactivity of lithium surface, making the film and lithium form a weak interface bond, avoiding excessive reaction, protecting the edges without contaminating the lithium surface; low temperature slows down the swelling / dissolution rate of film, but does not affect the isolation and protection effect of imprinting process, and resumes normal swelling / conversion behavior after entering the battery formation temperature, and participates in SEI construction normally; low temperature improves the dimensional stability of film, avoids alignment misalignment, film cracking or local peeling caused by thermal expansion and contraction, and ensures submicron-level cutting accuracy; low temperature also reduces film volatiles and outgassing, improves the vacuum / atmosphere stability of the cavity, avoids the rebound of moisture and oxygen content, and protects the lithium strip from oxidation.
[0029] In addition, the brittle lithium metal strip obtained by low-temperature treatment can further produce multiple beneficial synergistic effects on the functional protective film: brittle lithium only undergoes directional cleavage fracture under stress, without plastic extension and stretching, and will not stretch or tear the film, maintaining the integrity of the thin-layer isolation structure throughout the process; the cleavage fracture surface is flat and smooth, and the film can be uniformly transferred and adhered to the edge of the lithium cutting area, achieving synchronous edge passivation and avoiding local unprotected active interfaces; the residual internal stress after brittle lithium cutting is extremely low, and it will not squeeze and embed the film to generate debris and impurities, eliminating the risk of foreign matter contamination in the battery; the brittle lithium surface has few lattice defects and low active site density, which perfectly matches the weak affinity system of the film, eliminating local severe interface side reactions; the imprinting pressure required for brittle lithium cutting is significantly reduced, reducing the pressure load on the film, and the internal pore structure of the film is intact, ensuring the efficiency of subsequent electrolyte wetting, swelling and in-situ conversion, and fully exerting the function of constructing a stable SEI film.
[0030] This application completely avoids the aforementioned thermal, mechanical, and chemical damage through a combination of "low-temperature micro-imprinting precision separation" and "in-situ edge protection during cutting".
[0031] In some embodiments, the low-temperature treatment is performed at a temperature of -20°C to -35°C for 5-6 minutes.
[0032] Optionally, the temperature for low-temperature treatment can be any value between -20°C, -25°C, -30°C, -35°C, or -20°C to -35°C, and the duration of low-temperature treatment can be any value between 5 min, 5.5 min, 6 min, or 5 to 6 min.
[0033] It should be noted that the relationship between the temperature change during low-temperature treatment and the brittle lithium metal strip is shown in Table 1.
[0034] Table 1. Relationship between temperature change and brittle lithium metal strip.
[0035] This application involves subjecting lithium metal anode strips to low-temperature treatment, causing lithium to change from a plastic state to a brittle state. By relying on stress concentration to induce intergranular / cleavage fracture, a smooth cut without plastic deformation, burrs, or debris is achieved.
[0036] In some embodiments, the radius of the nanoscale cutting edge is <1 μm.
[0037] Optionally, the radius of the nanoscale cutting edge can be any value of 0.99μm, 0.9μm, 0.8μm, 0.7μm, 0.6μm, 0.5μm or <1μm.
[0038] Preferably, the radius of the nanoscale cutting edge is 0.2-0.6 μm.
[0039] In some embodiments, the tilt angle is 30-70°.
[0040] Optionally, the tilt angle can be any value between 30°, 40°, 50°, 60°, 70° or 30-70°.
[0041] It is important to note that the nanoscale cutting edge is designed as a wedge or similar structure with a specific angle (30-70 degrees), rather than a traditional vertical shearing edge. Through the synergistic design of nanoscale cutting edge precision and wedge angle, it enables the shearing or forming of ultra-thin, high-precision materials. Compared to traditional vertical shearing edges, the wedge-shaped nanoscale cutting edge design can effectively reduce material shearing force, reduce cutting edge wear, and improve processing accuracy and mold life. The angle selection needs to be combined with material properties (such as hardness and thickness) and processing requirements.
[0042] The structural diagram of the nanoscale cutting edge is shown below. Figure 1 As shown; the traditional vertical shear blade is structurally illustrated as follows. Figure 2 As shown.
[0043] In some embodiments, the temperature of the low-temperature micro-imprint cutting is -25°C to -35°C, and the pressure is 0.995-0.105 MPa.
[0044] Optionally, the temperature for low-temperature micro-imprint cutting can be any value between -20℃, -25℃, -30℃, -35℃, or -20℃--35℃, and the pressure can be any value between 0.995 MPa, 0.1 MPa, 0.105 MPa, or 0.995-0.105 MPa.
[0045] In some embodiments, during the low-temperature micro-imprint cutting, the downward speed of the cutting die with nanoscale cutting edges is 0.01-0.02 mm / s.
[0046] Optionally, the downward speed of the cutting die with nanoscale cutting edge can be any value between 0.01 mm / s, 0.015 mm / s, 0.02 mm / s, or 0.01-0.02 mm / s.
[0047] In some embodiments, the temperature in the low-temperature, low-oxygen, and low-humidity protective atmosphere is -28°C to -32°C, the oxygen content is ≤10ppm, and the moisture content is ≤5ppm.
[0048] Optionally, the temperature in the low-temperature, low-oxygen, and low-humidity protective atmosphere can be any value between -28°C, -29°C, -30°C, -31°C, -32°C, or -28°C to -32°C; the oxygen content can be any value between 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, 6 ppm, 7 ppm, 8 ppm, 9 ppm, 10 ppm, or ≤10 ppm; and the moisture content can be any value between 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, or ≤5 ppm.
[0049] In some embodiments, the entire process is carried out in an argon-protected environment (oxygen ≤10ppm, water ≤5ppm) to prevent lithium strip oxidation and contamination.
[0050] In some embodiments, the raw materials for the polymer flexible film include polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyoxyethylene copolymer, acrylonitrile copolymer, and acrylate polymer.
[0051] It is important to note that the polymer flexible film is solid at room temperature, highly flexible, and has a weak affinity for lithium interfaces. It is fully wetted and swollen by the electrolyte, with some chain segments slightly dissolving. During the formation process, it decomposes to release CO and CF functional groups, which participate in the construction of the SEI organic phase. The polymer flexible film is coated on the cutting edge of the mold, with controllable thickness, low cost, and strong compatibility with gel polymer electrolyte systems.
[0052] In some embodiments, the raw materials for the low-melting-point alloy film include bismuth-indium alloy, tin-bismuth-indium ternary alloy, and alkali metal alloy; In the bismuth-indium alloy, the mass ratio of bismuth to indium is 30-40:60-70; Optionally, the mass ratio of bismuth to indium in the bismuth-indium alloy can be any value between 30:70, 35:65, 40:60, or 30-40:60-70; Preferably, the mass ratio of bismuth to indium in the bismuth-indium alloy is 66.3:33.7; In the tin-bismuth-indium ternary alloy, the mass fractions of tin, bismuth, and indium are 12%-20%, 30%-35%, and 48%-55%, respectively, with a preferred mass fraction of tin, bismuth, and indium of 16.5%:32.5%:51%. Optionally, the mass fraction of tin in the tin-bismuth-indium ternary alloy can be any value between 12%, 14%, 16%, 18%, 20% or 12-20%, the mass fraction of bismuth can be any value between 30%, 31%, 32%, 33%, 34%, 35% or 30-35%, and the mass fraction of indium can be any value between 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55% or 48-55%. The alkali metal alloy includes at least one of lithium-sodium binary alloy, lithium-potassium binary alloy, and lithium-sodium-potassium ternary eutectic alloy.
[0053] The alkali metal alloy is a low-melting-point, non-toxic alloy that does not contain highly toxic components such as lead, cadmium, or mercury, and the alloy melting point is controlled between 40 and 80°C.
[0054] It is important to note that the low-melting-point alloy film is solid at room temperature, has excellent ductility, and exhibits controllable metallurgical affinity and strong adhesion to lithium metal. During low-temperature micro-imprinting and cutting, it buffers the cutting edge stress and undergoes slight melting and infiltration at the low temperature of battery operation or formation, alloying with lithium. Simultaneously, it is slightly corroded by the electrolyte to form alloy oxides or lithium alloy passivation layers, serving as inorganic reinforcing phases for the SEI. The melting point of the low-melting-point alloy film is controlled between 40 and 80°C to avoid melting at room temperature, triggering controllable conversion only under the low thermal field of formation.
[0055] In some embodiments, the raw materials for the fluorinated silicon organic-inorganic composite film include fluorinated silane modified SiO2, TiO2-doped polyvinylidene fluoride, and perfluoropolymer-silicate. In some embodiments, the mass ratio of fluorosilane-modified SiO2, TiO2-doped polyvinylidene fluoride, and perfluoropolymer-silicate is 10-40:30-60:10-40; The mass ratio of fluorosilane to nano-SiO2 in the fluorosilane-modified SiO2 is 1:5-15. Optionally, the mass ratio of fluorosilane to nano-SiO2 in fluorosilane-modified SiO2 can be any value between 1:5, 1:10, 1:15 or 1:5-15. Preferably, the mass ratio of fluorosilane to nano-SiO2 in fluorosilane-modified SiO2 is 1:10; The mass ratio of nano-TiO2 to PVDF in the TiO2-doped polyvinylidene fluoride is 1:8-20. Optionally, the mass ratio of nano-TiO2 to PVDF in TiO2-doped polyvinylidene fluoride can be any value between 1:8, 1:10, 1:15, 1:20 or 1:8-20. Preferably, the mass ratio of nano-TiO2 to PVDF in TiO2-doped polyvinylidene fluoride is 1:12; The mass ratio of perfluoropolymer to silicate matrix in the perfluoropolymer-silicate is 3-7:3-7.
[0056] Optionally, the mass ratio of the perfluoropolymer to the silicate matrix in the perfluoropolymer-silicate can be any value between 3:7, 4:6, 5:5, 6:4, 7:3, or 3-7:3-7.
[0057] Preferably, the mass ratio of perfluoropolymer to silicate matrix in the perfluoropolymer-silicate is 4:6.
[0058] It is important to note that fluorinated silicon organic-inorganic composite films provide flexibility, and inorganic particles enhance mechanical strength. The affinity between the F / Si groups and the lithium interface is controllable. After electrolyte wetting, the fluorine component decomposes to generate LiF (the optimal inorganic component for SEI), and the silicon component forms a Si-O-Li conductive network. The inorganic particles support the SEI framework. Highly stable SEI is generated directly in situ, with the best effect in suppressing lithium dendrites, making it suitable for high-voltage, long-cycle lithium metal batteries.
[0059] It should be noted that the thin layer of this application is an in-situ consumable and convertible functional layer, which simultaneously achieves three original functions: buffering hard contact during imprinting to avoid damage, burrs, and debris to lithium foil; having a weak affinity / weak reaction with lithium to avoid destroying the intrinsic structure of lithium; and being swollen / dissolved / converted in-situ by the electrolyte during formation to participate in the construction of a stable SEI film, ultimately leaving no foreign matter residue.
[0060] The core of this application lies in the synergistic innovation of low-temperature embrittlement, nano-edge micro-imprinting, and in-situ consumable passivation layer. Low temperature is not only the core process for changing the mechanical properties of lithium metal, but also ensures that the film can perform its protective and passivation functions normally at low temperatures through low-temperature resistant formulation and film formation process, ultimately achieving the integration of cutting and interface passivation, rather than simply adding cooling or ordinary anti-scratch film.
[0061] The second aspect of this application provides a lithium metal anode sheet, which is cut by the method for cutting lithium metal anode strips based on low-temperature microimprinting and in-situ edge passivation.
[0062] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0063] Example 1 This embodiment provides a method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation, as detailed below: S1 starts the low-temperature constant temperature chamber, sets the temperature to -30℃±2℃, turns on the argon protection system, and monitors the oxygen and moisture content in the chamber in real time. After the oxygen ≤10ppm and moisture ≤5ppm are reached, the temperature is kept constant for 10 minutes. S2: A flexible polymer film is pre-integrated on the side of the micro-imprinting die cutting edge (cutting edge radius < 1 μm). This film uniformly covers the cutting edge surface, with controllable thickness and no damage. The raw materials of the flexible polymer film include polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyoxyethylene copolymer, acrylonitrile copolymer, and acrylate polymer in a mass ratio of 25:15:20:15:25. The polyvinylidene fluoride-hexafluoropropylene copolymer was purchased from Arkema, France, and its model number was KynarFlex2801. Polyacrylonitrile was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with a molecular weight of Mw=150,000; The polyoxyethylene copolymer was purchased from NEI Corporation, USA, and its model number is NANOMYTE® H-polymer. The acrylonitrile copolymer was purchased from Daicel, Japan, model CP-20. The acrylate polymer was purchased from BASF, model number Acronal 4F.
[0064] The preparation method is as follows: 1. Solvent preparation: Anhydrous N,N-dimethylformamide (DMF) and acetone were mixed at a volume ratio of 7:3 to obtain a blended organic solvent; 2. Co-solution and stirring: Add the above five polymers to the mixed solvent in the above proportions, and control the solid content to 10wt%; keep the temperature in a 45℃ water bath and stir mechanically for 8 hours until the system is completely transparent and free of particles, and then let it stand under vacuum for 30 minutes to remove bubbles inside the solution. 3. Edge pretreatment: The cutting edge of the tungsten carbide wedge mold with a cutting radius of 0.5μm and an inclination angle of 50° is subjected to plasma cleaning (argon plasma, power 120W, treatment time 3min) to remove oil and oxide layer on the cutting edge surface and improve the adhesion between the film and the substrate. 4. Micro-dip coating: The precision dip coating process is adopted. The die cutting edge is vertically immersed into the polymer precursor liquid, soaked for 15 seconds, and then pulled upward at a uniform speed of 2 mm / s. The film thickness after a single dip coating is 0.8-1.5 μm. The dip coating is repeated twice to control the total dry film thickness of 1-3 μm without changing the original wedge geometry of the cutting edge. 5. Gradient low-temperature curing: ① First stage low-temperature pre-baking: 45℃ vacuum oven for 40 minutes to slowly evaporate most of the organic solvents and avoid rapid shrinkage of the film to prevent micro-cracks. ② Second stage of medium temperature setting: vacuum heat treatment at 65℃ for 90 minutes to complete the cross-linking and setting of polymer chain segments, ensuring that the film maintains high flexibility in a low temperature environment of -32℃; 6. Cooling and standing: After curing, the furnace is naturally cooled to room temperature and then placed in an argon-sealed chamber for 12 hours to eliminate residual internal stress in the film and obtain a consuming / transferable polymer flexible functional film with uniform load on the edge side.
[0065] The mold was then installed on the piezoelectric ceramic drive platform, the vision alignment camera was activated, the parallelism between the mold cutting edge and the stage was calibrated (error ≤ 0.1 μm), the XY positioning reference point was set, and the positioning repeatability was tested 10 times consecutively (deviation ≤ ± 0.1 μm). S3: Connect the pressure sensor to the mold, set the target pressure to 0.1MPa, simulate the pressing action to test the pressure stability (fluctuation ≤ ±0.005MPa), and simultaneously set key parameters such as pressing speed and holding time; S4: Align the infrared temperature probe with the stage and the cutting edge of the mold to monitor the temperature in real time and ensure that it is consistent with the set temperature of the low temperature chamber (temperature difference ≤ 0.5℃). S5: Take a pre-treated lithium strip that is free of oxidation and impurities, and quickly place it in a low-temperature constant temperature chamber (exposed to air for no more than 30 seconds); lay the lithium strip flat on the vacuum adsorption stage, adjust its position so that its edge is aligned with the stage positioning line, and start the vacuum adsorption system (adsorption pressure 0.02~0.03MPa). Observe under a microscope to confirm that the lithium strip is flat, without warping or slippage. The time interval from placing the lithium strip in the low-temperature constant temperature chamber to performing low-temperature micro-imprint cutting is 6 seconds. min ; S7: Use an infrared temperature probe to remeasure the surface temperature of the lithium strip to ensure that it is consistent with the ambient temperature inside the chamber (-30℃±2℃); if the temperature deviation is too large, let it stand for 5 minutes before proceeding with the subsequent operations. S8: Activate the vision alignment system. The camera captures the preset positioning marks on the lithium strip surface and the contour of the die cutting edge. The software automatically calculates the alignment deviation and drives the piezoelectric ceramic platform to adjust the die position in the XY direction (X direction refers to the lithium strip feeding length direction, and Y direction refers to the lithium strip width laterally) in real time until the cutting edge is precisely aligned with the preset separation contour of the lithium strip (deviation ≤ ±0.1μm). The tilt angle between the cutting edge and the vertical direction is 50°. Manually confirm the alignment effect by magnifying with a microscope. If there is a deviation, fine-tune the positioning parameters to ensure that the cutting edge and the separation contour are completely fitted without any offset or deflection. S9: Start the imprinting system and drive the die downwards in the Z direction at a speed of 0.01 mm / s according to preset parameters, gradually applying pressure to 0.1 MPa. During the process, the flexible polymer film material on the side of the cutting edge isolates the cutting edge from direct hard contact with the lithium strip, avoiding scratching the lithium strip and generating burrs and debris. At the same time, the pressure, indentation amount, and temperature data are monitored in real time to ensure no abnormal fluctuations. After reaching the target pressure, hold the pressure for 4 seconds. Utilize the stress concentration effect at the tip of the die cutting edge to induce brittle fracture in the micro-region below the lithium strip cutting edge. After the pressure holding period, slowly depressurize to 0 MPa at a speed of 0.01 mm / s, and then drive the die to reset in the Z direction (reset accuracy ±0.1 μm) to avoid scratching the lithium strip surface during reset, resulting in the cut lithium metal anode strip.
[0066] Example 2 The difference from Example 1 is that the film on the side of the cutting edge is a low-melting-point alloy film, and the integration method of the low-melting-point alloy film is an inert atmosphere micro-thermal dip coating method. 1. Preparation of alloy melt: Indium-bismuth alloy, indium-bismuth-tin ternary alloy, and low-melting-point non-toxic alkali metal alloy are mixed according to the following proportions. In the bismuth-indium alloy, the mass ratio of bismuth to indium is 33.7:66.3. In the tin-bismuth-indium ternary alloy, the mass fractions of tin, bismuth, and indium are 16.5%, 32.5%, and 51%, respectively. The alkali metal alloys include lithium-sodium binary alloy with a mass ratio of 25:75, lithium-potassium binary alloy with a mass ratio of 20:80, and lithium-sodium-potassium ternary eutectic alloy with a mass ratio of 15:35:50. The argon-sealed crucible is heated to 20°C above the alloy's melting point and stirred at a constant temperature for 10 minutes to remove air bubbles inside the melt. Argon gas is continuously introduced to isolate oxygen and prevent the alloy from oxidizing and producing slag.
[0067] 2. Mold preheating and masking: The tungsten carbide mold is preheated to 45°C. A high-temperature resistant polyimide mask is used to completely cover the non-cutting edge area of the mold, exposing only the wedge-shaped cutting bevel. Avoid covering the non-working surface of the mold substrate with an alloy film.
[0068] 3. Precision micro-immersion coating: Immerse the mold cutting edge vertically downwards into the molten alloy liquid for 15 seconds, and then pull it vertically upwards at a uniform speed (1.5 mm / s); relying on the surface tension of the melt, a continuous ultra-thin liquid alloy film is formed on the inclined surface of the cutting edge.
[0069] 4. Rapid cooling in an inert atmosphere: Immediately after lifting, the film is moved into an argon cryogenic cooling stage (20℃) for rapid solidification and shaping, controlling the film thickness to 1~2.5μm; the mask is removed to eliminate trace alloy overflow at the edge of the cutting edge, ensuring that the geometric accuracy of the cutting edge tip remains unchanged.
[0070] Example 3 The difference from Example 1 is that the film on the side of the cutting edge is a fluorinated silicon organic-inorganic composite film, and the integration method of the fluorinated silicon organic-inorganic composite film is a sol-gel precision micro-immersion coating gradient low-temperature curing method, the specific steps of which are as follows: 1. Precision pretreatment of the die cutting edge: Take a tungsten carbide cutting die with a cutting edge radius of 0.5μm and an inclination angle of 50°; clean it sequentially with anhydrous isopropanol and anhydrous acetone for 8 minutes each to remove surface cutting oil and dust; move it into a vacuum chamber for argon plasma activation (power 110W, argon partial pressure 0.25Pa, treatment for 3 minutes) to generate trace hydroxyl sites on the beveled surface of the cutting edge, thereby improving the adhesion between the fluorosilicone film and the substrate; cover the non-cutting edge plane with a high-temperature resistant polyimide mask, leaving only the cutting bevel exposed.
[0071] 2. Preparation of fluorosilicone composite sol: Fluorosilane-modified SiO2, TiO2-doped polyvinylidene fluoride (PVDF), and perfluoropolymer-silicate were mixed at a mass ratio of 30:45:25. Specifically, the mass ratio of fluorosilane to nano-SiO2 in the fluorosilane-modified SiO2 was 1:10; the mass ratio of nano-TiO2 to PVDF in the TiO2-doped PVDF was 1:12; and the mass ratio of perfluoropolymer to silicate matrix in the perfluoropolymer-silicate was 4:6. Hydrofluoroether and anhydrous ethanol were used as the blending solvent at a volume ratio of 2:1, and the solid content of the system was controlled at 8 wt%. The mixture was mechanically stirred at room temperature for 4 hours, then ultrasonically dispersed at 40 kHz for 30 minutes, and finally vacuum-sterilized for 25 minutes to remove bubbles, resulting in a homogeneous and stable fluorosilicone hybrid sol.
[0072] 3. Directional Micro-Dip Coating: A CNC lifting dip coating machine is used. The mold is fixed vertically, and only the exposed wedge-shaped cutting edge is immersed in fluorosilicone sol for 12 seconds. The mold is then lifted vertically upward at a uniform speed of 1.8 mm / s, and a uniform wet film is formed on the cutting edge due to the low surface tension of the sol. The wet film from a single lift corresponds to a dry film thickness of 0.6-1.2 μm. The dip coating is repeated twice, and the total dry film thickness is finally controlled to be 1-2.5 μm. The film layer is ultra-thin and does not cover the tip of the cutting edge, thus completely preserving the nanoscale stress concentration arc.
[0073] 4. Gradient-segmented low-temperature curing: Low-temperature pre-baking section: 40℃ vacuum oven for 50 minutes to slowly evaporate hydrofluoroether and ethanol solvent, preventing rapid solvent evaporation from causing film shrinkage and cracking; Medium-temperature crosslinking and shaping stage: Vacuum heat preservation at 60℃ for 100min, fluorosilane undergoes hydrolysis and condensation to form a Si-O-Si crosslinking network, organic phase and inorganic filler are tightly hybridized, ensuring that the film maintains high flexibility at a low temperature of -32℃; the highest curing temperature throughout the process is only 60℃, there is no risk of high-temperature tempering, and it will not change the nano-arc curvature and wedge angle of the tungsten carbide cutting edge.
[0074] 5. Post-treatment stress relief molding: After curing, the furnace is naturally cooled to room temperature. The argon-sealed chamber is left to stand for 10 hours to eliminate residual stress from cross-linking inside the film. The surface mask is removed, and a small amount of hydrofluoric acid is applied to a lint-free cloth to gently wipe the tip of the blade to ensure that there is no thick film passivation at the tip. This results in a transferable, consumable fluorinated silicon organic-inorganic composite film that combines buffer protection and electrochemical passivation functions.
[0075] Comparative Example 1 The difference from Example 1 is that the time interval between the lithium strip being placed in the low-temperature constant temperature chamber and the low-temperature micro-imprint cutting is 2-3 minutes.
[0076] Comparative Example 2 The difference from Example 1 is that in step S9, the cutting edge is moved downward in a vertical direction.
[0077] Comparative Example 3 The difference from Example 1 is that no flexible polymer film is provided on the surface of the cutting edge.
[0078] Comparative Example 4 The difference from Example 1 is that the radius of the cutting edge is 1.5 μm.
[0079] Edge detection was performed on the cut lithium metal anode strips obtained from the above embodiments and comparative examples. The edge detection method was as follows: 1. Sample pretreatment: The cut lithium strips were placed in an argon glove box with oxygen content ≤10 ppm and moisture content ≤5 ppm throughout the sampling process to avoid oxidation of the fresh lithium edges; the sample length was uniformly cut to 50 mm, and the edge to be tested was free from contact and external pressure contamination. 2. Observation equipment: It adopts an ultra-high resolution laser confocal microscope, equipped with a 1000x metallurgical objective lens and a three-dimensional contour scanning module; 3. Observation steps: The lithium strip is flattened and adsorbed onto the vacuum stage. After fixation, 10 sets of three-dimensional contour images of different positions are continuously acquired on the cut surface; the scanning length of each set is 2 mm, and the longitudinal scanning accuracy is 0.01 μm. 4. Quantitative testing indicators: maximum burr height at the edge, flatness of the cross-section (average difference in edge unevenness), maximum plastic deformation at the cut edge, width of plastic curl at the edge, number of microcracks / hidden cracks at the cross-section, and uniformity and integrity of the edge film coverage. 5. Judgment criteria: The average value of 10 sets of data is taken as the final test result of a single sample, and the differences in edge morphology and size defects of each group are compared.
[0080] The specific edge detection results are shown in Table 2.
[0081] Table 2 Edge Detection
[0082] The cut lithium metal anode sheets obtained in the above embodiments and comparative examples were combined with NCM811 cathode sheets, commercial 7µm high-porosity PE separators, and commercial electrolytes to construct a small 9.0Ah pouch battery.
[0083] The electrochemical performance of the aforementioned small pouch batteries was tested (0.2C formation, 1C cycle test and 3C rate discharge test), and the specific results are shown in Table 3.
[0084] 0.2C formation: Under 25℃ conditions, charging and discharging at a rate of 0.2C, with a voltage range of 2.5V~4.2V; 1C Cyclic Test: At 25℃, charge at 1C constant current to the upper limit voltage, cut off current at 0.05C, discharge to 2.5V, cycle 500 times and record capacity retention rate; 3C rate discharge test: Under 25℃ conditions, 1C constant current and constant voltage charging to 4.2V, 0.05C current cutoff, 3C constant current discharge to 2.5V and record 3C discharge capacity; Charge transfer impedance: The AC impedance of the battery cell was measured using a CHI660E electrochemical workstation at 25℃ and 50% SOC. The test frequency range was 0.1Hz to 10Hz. 6 Hz, the charge transfer impedance is obtained by fitting a curve.
[0085] Table 3 Electrochemical Performance Tests
[0086] analyze: In embodiments 1, 2, and 3 of this invention, polymer flexible films, low-melting-point alloy films, and fluorine-silicon organic-inorganic composite films are respectively used. The entire process is strictly implemented as follows: -32 ℃ low-temperature constant temperature pretreatment for 5~6 min, wedge-shaped inclined downward pressure cutting, and cutting edge radius of 0.2-0.6μm.
[0087] Example 1 (polymer flexible film): The maximum burr at the edge is 0.21 μm, and the film coverage is 96%; the capacity retention rate after 500 cycles is 83.6%. The organic polymer film has excellent buffering and isolation effects, and can form an organic component SEI passivation layer after cutting; however, the pure organic film has low mechanical strength and general resistance to low-temperature hardening, so its overall performance is the lowest among the three examples.
[0088] Example 2 (low melting point alloy film): The maximum edge burr is 0.18 μm, and the film coverage is 98%; the capacity retention rate after 500 cycles is 87.1%. The metal alloy is flexible and has better buffering and compression resistance than pure polymer film; after the battery formation is heated, the alloy layer and lithium metal undergo in-situ alloying to generate a lithium alloy inorganic passivation phase, and the interface stability is better than that of a simple organic SEI.
[0089] Example 3 (fluorinated silicon organic-inorganic composite film): The maximum edge burr is 0.16 μm, and the film coverage is 99%; the capacity retention rate after 500 cycles reaches 90.4%. The organic matrix ensures the flexibility of the film at low temperatures, while the inorganic modified filler can induce the formation of LiF and Si-O-Li composite SEI at the lithium edge; the fluorinated silicate component can reduce the interfacial impedance, effectively homogenize the negative electrode surface current, and inhibit lithium dendrite initiation. The morphology and electrochemical properties are both optimal.
[0090] Comparative Example 1 had a low-temperature holding time of only 2-3 minutes. The burr height was 0.95 μm, with 3 microcracks and a film coverage of 75%. The initial efficiency was 88.5%, and the capacity retention after 500 cycles was 63.7%, with overall performance between Example 1 and Comparative Example 1. Insufficient holding time only cooled the surface of the lithium foil, leaving the lithium core at a high temperature and still plastic. During cutting, the surface lithium layer fractured brittlely, and the inner lithium layer was compressed, resulting in burrs and curling edges. Pressure and impact caused the transfer protective film to shift and break, and the passivation layer at the cut surface lacked integrity. The unstable negative electrode interface exacerbated electrolyte side reactions, increased voltage polarization, and increased the risk of dendrite growth.
[0091] Comparative Example 2 shows a cutting edge using a 90° vertical downward cut. The burr height is 1.32 μm, there are 5 cracks, and the film coverage is 68%; the initial coulombic efficiency is 85.1%, but the capacity retention after 500 cycles is only 54.8%. This application relies on the inclined wedge-shaped cutting edge to generate localized stress concentration, driving the brittle cleavage of lithium metal. The vertical downward pressure is a form of hard extrusion shearing, with the front of the cutting edge strongly compressing the lithium strip cut surface, shearing and tearing the protective film on the side of the cutting edge; the lithium edge is compressed and curled, creating notch defects. The uneven passivation layer causes uneven current distribution on the negative electrode surface, increased electrochemical polarization, and decreased cycle stability.
[0092] Comparative Example 3 lacked a polymer flexible protective film on its cutting edge surface. The edge film coverage was 0%, with 1.14 μm burrs and four microcracks observed. The initial coulombic efficiency was 83.4%, and the capacity retention after 500 cycles was as low as 48.3%. The hard tungsten carbide cutting edge directly scraped against fresh lithium metal, generating lithium debris and edge damage during the cutting process. The lack of a transferable buffer-passivation film meant that the freshly cut lithium surface directly contacted the electrolyte, leading to irreversible consumption over a long period. The rough negative electrode surface easily induced lithium dendrites, significantly increasing charge transfer impedance and resulting in poor long-cycle performance.
[0093] Comparative Example 4 shows an increased cutting edge radius of 1.5 μm. The burr height is 1.66 μm, with 6 microcracks and a protective film coverage of only 53%. The initial coulombic efficiency is 84.6%, and the capacity retention after 500 cycles is 51.6%. The stress concentration effect disappears after passivation of the nano-cutting edge tip; even though the lithium metal has undergone low-temperature embrittlement treatment, it still undergoes plastic extrusion deformation under pressure, resulting in an uneven cut surface. The wide, rounded cutting edge rubs and tears the protective film on the cutting edge surface; the lithium edge lacks a complete in-situ passivation film; the stability of the negative electrode-electrolyte interface deteriorates, polarization increases, and lithium dendrites are more prevalent.
[0094] The cut surfaces of the lithium metal anodes in the three sets of embodiments have low burrs, almost no plastic curling, and no microcracks. The cutting edge functional film can be completely transferred to the fresh cut surface of the lithium strip to construct an in-situ passivation SEI film. The corresponding assembled lithium battery has high initial coulombic efficiency, low charge transfer impedance, and excellent long-term cycle stability.
[0095] The four comparative sets of samples only changed one core process parameter, resulting in defects such as burrs, curled edges, microcracks, and damage and detachment of the transfer protective film at the cutting edge; the exposed highly active fresh lithium continuously undergoes irreversible side reactions with the electrolyte, and the negative electrode... The passivation layer at the electrolyte interface is uneven, the current distribution is unbalanced, and ultimately all electrochemical properties show significant degradation.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0097] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation, characterized in that, include: The lithium metal anode strip was subjected to low-temperature treatment to obtain a brittle lithium metal strip. Using a cutting die with nanoscale cutting edge, the brittle lithium metal strip is cut at a low temperature, low oxygen and low humidity protective atmosphere along a direction at an angle to the vertical to obtain the cut lithium metal anode strip. The cutting die with nanoscale cutting edge includes a cutting edge substrate and a functional protective film disposed on the surface of the cutting edge substrate. The functional protective film is in direct contact with the brittle lithium metal strip during the low-temperature micro-imprint cutting. The functional protective film includes at least one of polymer flexible film, low melting point alloy film, and fluorine-containing silicon organic-inorganic composite film.
2. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, The low-temperature treatment is performed at a temperature of -20°C to -35°C for 5-6 minutes.
3. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, The radius of the nanoscale cutting edge is <1μm.
4. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, The included angle of inclination is 30-70°.
5. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, The temperature for the low-temperature micro-imprint cutting is -25℃ to -35℃, and the pressure is 0.995-0.105MPa.
6. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, During the low-temperature micro-imprint cutting, the downward speed of the cutting die with nanoscale cutting edge is 0.01-0.02 mm / s; And / or, the temperature in the low-temperature, low-oxygen, and low-humidity protective atmosphere is -20°C to -35°C, the oxygen content is ≤10ppm, and the moisture content is ≤5ppm.
7. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, The raw materials for the polymer flexible film include polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyoxyethylene copolymer, acrylonitrile copolymer, and acrylate polymer.
8. The method for cutting lithium metal anode strips based on low-temperature micro-imprinting and in-situ edge passivation according to claim 1, characterized in that, The raw materials for the low-melting-point alloy film include bismuth-indium alloy, tin-bismuth-indium ternary alloy, and alkali metal alloy; In the bismuth-indium alloy, the mass ratio of bismuth to indium is 30-40:60-70; In the tin-bismuth-indium ternary alloy, the mass fractions of tin, bismuth, and indium are 12%-20%, 30%-35%, and 48%-55%, respectively. The alkali metal alloy includes at least one of lithium-sodium binary alloy, lithium-potassium binary alloy, and lithium-sodium-potassium ternary eutectic alloy.
9. The method for cutting lithium metal anode strips based on low-temperature microimprinting and in-situ edge passivation according to any one of claims 1-8, characterized in that, The raw materials for the fluorinated silicon organic-inorganic composite film include fluorinated silane modified SiO2, TiO2-doped polyvinylidene fluoride, and perfluoropolymer-silicate. The mass ratio of fluorinated silane to nano-SiO2 in the fluorinated silane-modified SiO2 is 1:5-15. The mass ratio of nano-TiO2 to PVDF in the TiO2-doped polyvinylidene fluoride is 1:8-20. The mass ratio of perfluoropolymer to silicate matrix in the perfluoropolymer-silicate is 3-7:3-7.
10. A lithium metal anode sheet, characterized in that, It is cut by the lithium metal anode strip cutting method based on low temperature microimprinting and in-situ edge passivation as described in any one of claims 1-9.